Multi‐scale experimental investigations of the thermal degradation of pine needles. (12th October 2016) - Fateh, T.; Richard, F.; Zaida, J.; Rogaume, T.; Joseph, P.
Summary: In this work, the thermal degradation of pine needles (from a Mediterranean species) was studied using a thermogravimetric analysis and cone calorimeter that were coupled to Fourier transform infrared spectrometer. The thermogravimetric analyses were carried out at four heating rates, in both air and nitrogen atmospheres. The evolution of gaseous components, mass loss and mass loss rate were recorded as a function of time and temperature. In order to account for the observed behaviours of the materials, we have also proposed a mechanism for the thermal degradation of pine needles, by primarily analysing the evolutions of both mass loss rate and gaseous components under nitrogen and air atmospheres. The kinetic parameters were subsequently estimated by using a genetic algorithm method. The cone calorimetric measurements were mainly conducted with a view to investigating the influence of thermal transfer processes, occurring in a porous bed of pine needles with regard to its thermal degradation. The experiments were conducted at five external heat fluxes under a well‐ventilated atmosphere. Measurements consisted of the mass loss, mass loss rate and the amount of gaseous emissions. The main gases emitted during the thermal degradation and the combustion of the pine needles were found to be CH4, CO, CO2, NO and water vapour. In addition, the evolution of the temperature was measured by using a set of five thermocouples, placed in a vertical position at the centreline of the sample. The results obtained showed that the bed of pine needles behaved as a thermally thick fuel. On the contrary, at higher external heat fluxes, the sample behaved as a thermally thin sample. Copyright © 2016 John Wiley & Sons, Ltd.